2017
DOI: 10.5455/njppp.2017.7.0514113052017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices toward Jan Aushadhi scheme

Abstract: Background: Increased health-care expenses are a major concern in a country like ours where economic conditions are on the lower side. The Government of India to control the increased health-care expenses launched the Jan Aushadhi scheme in April 2008 by providing low-cost generic medicine. However, the results have not been as expected. Aims and Objectives: The current study was designed to have insight into this problem by studying knowledge, attitude, and practices (KAP) among doctors and patients. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Almost 83.6% of physicians said that there should be a generic medicine store in every hospital. Our findings are also concurrent with the study conducted by Sadiq et al, [11] who found that 66.66% of the prescribers had the knowledge that the Jan Aushadhi [12] in their research observed that 90% of patients believed that generic medicines are as effective as brand medicines and only 10% of patients said that side effects are more with generic medicines and considered them to be much cheaper than brand medicines, which are concurrence to our study. In the current study, 89.5% are of the opinion that generics are cheaper than branded ones.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Almost 83.6% of physicians said that there should be a generic medicine store in every hospital. Our findings are also concurrent with the study conducted by Sadiq et al, [11] who found that 66.66% of the prescribers had the knowledge that the Jan Aushadhi [12] in their research observed that 90% of patients believed that generic medicines are as effective as brand medicines and only 10% of patients said that side effects are more with generic medicines and considered them to be much cheaper than brand medicines, which are concurrence to our study. In the current study, 89.5% are of the opinion that generics are cheaper than branded ones.…”
Section: Discussionsupporting
confidence: 82%
“…Nearly 80.7% of doctors believe that government should give tax benefit to generic manufacturers to promote more easier generic prescribing and usage. Our results are similar to the findings of Sadiq et al, [11] where all doctors agreed to the fact that Jan Aushadhi medical store should be available in every hospital and awareness regarding its use must be encouraged while 91.66% agreed that government should come up with stringent laws for its use.…”
Section: Discussionsupporting
confidence: 82%
“…7 87.5% of the participants preferred generics for personal/family use in contrast to a study by Khadke VV et al, where only 57 % preferred. 7 95.3% of the participants suggested media advertising and publicity on generic drugs similar to studies done by Desai S et al, and Sadiq S et al 3,10…”
Section: Discussionsupporting
confidence: 70%
“…Jan Aushadhi centers in the country provide generic medicines of 230 different kinds of drug formulations. 3 The Red Cross and a few other non-government organisations run these drug stores. In Government General Hospital, Guntur a Jan Aoushadi generic outlet was established to encourage generic drug use.…”
Section: Introductionmentioning
confidence: 99%
“…There can be certain dangers, issues, and challenges of selling drugs online. Illegal or unethical online pharmacies, sources of obtaining medicine, substitution of drug based on availability, and inability to execute order due to lack of legitimate prescription were among the issues [10].…”
Section: Literature Reviewmentioning
confidence: 99%